ON THE ISSUE OF IMPROVING THE COMPOSITION OF THE DRIVE SCHEME OF THE VIBRO-FRICTION SEPARATOR OF SEED MIXTURES (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2026)
The paper considers the issues of improving the design of vibrofriction separators intended for separation of hard-to-separate grain mixtures, namely, the arrangement of the drive scheme in the oscillatory motion of the working body by kinetically and electrically unconnected vibration exciters. It is proved that in the known vibrofriction separators, the process of adjusting the directional angle of oscillations is associated with the need to move it along the vibrating table by a value that is an undetermined parameter in advance and is carried out by selecting it in the process of adjustment.The paper proposes an improvement to the drive of the vibrofriction separator by installing two self-synchronizing vibration exciters positioned on the same platform and equidistant from the center of gravity of the vibrating table. These exciters are equipped with additional curved skids, which simplify the adjustment of the oscillation directional angle, reduce dissipative losses, and decrease the overall dimensions of the vibrofriction separator.
Keywords: vibration exciters; drive; layout; separator; adjustment; direction angle of oscillations